Antioxidant Properties and Effects of Formulation Variables on Ceiba pentandra Microspheres (Nigerian Journal of Pharmaceutical Research, 2024)
Background: New drug delivery techniques have improved therapeutic and physicochemical properties of herbal medicines.Objective: Extracts of Ceiba pentandra (CP) leaf have been evaluated for antioxidant properties with the aim of formulating them into microspheres and studying release of flavonoid from the dosage form. Materials and Methods: Microspheres were prepared from extracts of CP using ionotropic gelation method. Formulation parameters were varied to produce A1 to A8. Microspheres were evaluated for size, shape, yield, micrometrics, swelling, entrapment efficiency, and flavonoid release characteristics. Factorial experimentation design was used to determine the individual and interactive effects of the formulation variables on entrapment efficiency and flavonoid release. Results were analysed using ANOVA at p≤0.05.Results: The extract contained flavonoids. Microspheres were discrete, porous, spherical, with good flow. Microspheres swelled moderately and eroded within 3 hours. Entrapment efficiencies ranged from 4.17 to 19.2 %. All Formulations released 80 % of flavonoid within 6 hours, except A2, A3 and A8 which sustained flavonoid release for 24 – 26 hours. Concentration of polymer had the highest positive effect, while stirring speed had the highest negative effect on microsphere entrapment efficiency. Effect of curing time on entrapment efficiency was positive but insignificant. Polymer concentration and curing time had negative effects on flavonoid release, while stirring speed showed a positive effect.Conclusion: Extracts of Ceiba pentandra leaves possess antioxidant constituents and could be formulated into microspheres of good physicochemical properties. Concentrations of polymer and curing time are important parameters that should be considered in the formulation of CP into microspheres with sustained release potentials.